The Influence of Product Brand Image on Purchasing Decision on Smartfren Internet Modem: Case Study at Indo Global Mandiri University, Palembang - Dwiningrum, Nurfianita; Marnisah , Luis; Handayani, Susi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
This study aims to examine the effect of brand image on purchasing decisions for Smartfren internet modems. Data were collected through questionnaires on 95 students of the Indo Global Mandiri University class of 2018. The statistical analysis method used simple linear regression. The result of the investigation evidences that brand image has a positive and significant effect on purchasing decisions for Smartfren internet modems. Based on the result, Smartfren should increase the brand image of their internet modems to increase sales. This research was only conducted on students of the Indo Global Mandiri University. Research results may be inapplicable in other research samples.